Fostering the Value of Religious Tolerance among Students through the Development of Potential Issues: A Review of Bibliometric Analysis - Huda, Ali Anhar Syi'bul; Nurhuda, Abid; Lathif, Nur Muhammad (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2024)
Religious tolerance is a global priority amidst diverse beliefs and interests. This research explores potential issues in student religious tolerance for educational stakeholders. The study uses a qualitative bibliometric approach with descriptive data analysis. Findings indicate an increasing but modest trend in religious tolerance research over the past 14 years (2010-2024), peaking in 2023 with 65 articles. Electronic journals (e-journals) are the largest source of such research, with 150 publications. Four productive researchers from Jambi University produced two publications: Arizal Dwi Kurniawan, Nur Aini, Marlina Susanti, and Anisa Andrian. The study identifies several potential future research areas in student religious tolerance, including religion, mutual respect, analysis, tolerance, character education, data, institutions, teachers, Islamic religion, literature review, Islamic education, school, challenges, literacy, strategy, teacher, multicultural Islamic education, student ability, integration, multicultural education, society, tolerance, literature study, child, and concept.